2015
DOI: 10.1039/c4cp02709d
|View full text |Cite
|
Sign up to set email alerts
|

Water-mediated interactions between trimethylamine-N-oxide and urea

Abstract: The amphiphilic osmolyte trimethylamine-N-oxide (TMAO) is commonly found in natural organisms, where it counteracts biochemical stress associated with urea in aqueous environments. Despite the important role of TMAO as osmoprotectant, the mechanism behind TMAO's action has remained elusive. Here, we study the interaction between urea, TMAO, and water in solution using broadband (100 MHz-1.6 THz) dielectric spectroscopy. We find that the previously reported tight hydrogen bonds between 3 water molecules and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 49 publications
15
80
0
Order By: Relevance
“…We also observed that the influence of Lysozyme on the structure of TMAO is more profound at lower osmolyte concentration, and decreases rapidly for higher protein concentrations, supporting the hypothesis that TMAO is preferentially excluded from the protein surface and that it prefers to strongly bind 2-3 water molecules in solutions. 63,66,68 In the case of Proline, spectral results indicate that Pro, although being a good protein stabilizer, interacts directly with the protein surface, and that the carboxyl group of Proline molecule plays a dominant role in these interactions ( Figure 8B). MD simulations confirm preferential binding of Proline to the Lysozyme surface.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that the influence of Lysozyme on the structure of TMAO is more profound at lower osmolyte concentration, and decreases rapidly for higher protein concentrations, supporting the hypothesis that TMAO is preferentially excluded from the protein surface and that it prefers to strongly bind 2-3 water molecules in solutions. 63,66,68 In the case of Proline, spectral results indicate that Pro, although being a good protein stabilizer, interacts directly with the protein surface, and that the carboxyl group of Proline molecule plays a dominant role in these interactions ( Figure 8B). MD simulations confirm preferential binding of Proline to the Lysozyme surface.…”
Section: Discussionmentioning
confidence: 99%
“…Spectra at 0.8–50 GHz were recorded using an open‐ended coaxial cell based on 1.85 mm connectors . The thus obtained spectra were complemented at frequencies at 10 MHz to 400 MHz using a cut‐off type coaxial cell . All experiments were performed at ambient temperature (295±2 K).…”
Section: Methodsmentioning
confidence: 99%
“…Chemical compounds such as carbohydrates, polyols, amino acids, methylamines or TMAO are known to stabilize the folded state of proteins and therefore are often designated as chemical chaperones, whereas those that favor the unfolded state, such as urea, are known as denaturants. Specifically, TMAO is well-known to act as a protecting osmolyte by stabilizing the folded state of proteins at high pressures (and also high temperatures), thus counteracting their unfolding [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] . In that sense, TMAO could be viewed as an antagonist to high-pressure protein denaturation.…”
Section: Introductionmentioning
confidence: 99%